Developing a cosmetic series: Results from theESSCAnetwork, 2009-2018 - Horton, Emma; Uter, Wolfgang; Geier, Johannes; Ballmer-Weber, Barbara; Bauer, Andrea; Bircher, Andreas; Dickel, Heinrich; Gimenez-Arnau, Ana; Goncalo, Margarida; John, Swen Malte; Mahler, Vera; Schuttelaar, Marie L. A.; et al. (Contact Dermatitis, 2020)
Background There is considerable variability across European patch test centres as to which allergens are included in local and national cosmetics series. Objectives To propose a standardized, evidence-based cosmetic series for Europe based on up-to-date analysis of relevant contact allergens. Methods We collated data from the European Surveillance System on Contact Allergies (ESSCA) from 2009 to 2018 to determine which cosmetic allergens produce a high yield of contact allergy. Contact allergens with a prevalence of >0.3% that were considered relevant were included. Rare contact allergens were excluded if deemed no longer relevant or added to a supplemental cosmetic series for further analysis. Results Sensitization prevalences of 39 cosmetic contact allergens were tabulated. Thirty of these allergens yielded >0.3% positive reactions and are therefore included in our proposed European cosmetic series. Six were considered no longer relevant and therefore excluded. Three were included in a supplementary European cosmetic series. An additional nine allergens were included in either the core or supplemental European cosmetic series following literature review. Conclusion We have derived a potential European cosmetic series based upon the above methods. This will require ongoing investigation based upon the changing exposure profiles of cosmetic allergens as well as new and evolving substances.
CRIS-Team WoS Importer:2020-10-16